Cashless payments and tax evasion: Evidence from VAT gaps in the EU - Albrecht Bohne; Antonios M. Koumpias; Annalisa Tassi (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2023)
This paper explores the connection between the proliferation of cashless, or e-money, payments and value-added tax (VAT) compliance. We present both visual and descriptive evidence that illustrates a negative correlation between e-money use and VAT evasion, proxied by the VAT compliance gap for countries in the European Union, from 2001 until 2021. We find that increased e-money usage by 100 percentage points (pp) is associated with a reduction in the VAT gap of 0.3pp or 1.92% of the aggregate VAT compliance gap over time. Moreover, we contribute a novel estimate of the causal impact of cashless payments on VAT evasion during the COVID-19 public health emergency. We identify a link between mobility restrictions in the European Union and reductions in VAT compliance gaps, facilitated by changes in payment norms. An estimated rise of 1pp or 5.51% in e-money use results in an 11.9% reduction in the VAT compliance gap. Our findings suggest that changes in transaction payment behavior such as the adoption of cashless payments may yield significantly more tax revenues by curbing non-compliance. Policies aimed at promoting e-money usage and limiting cash circulation are relevant steps forward in this direction.
Keywords: H26; K42; 330; Tax evasion; VAT gap; cashless payments; e-money; mobility restrictions; COVID-19 pandemic